2017
DOI: 10.3892/ol.2017.7516
|View full text |Cite
|
Sign up to set email alerts
|

ABT‑737 and pictilisib synergistically enhance pitavastatin‑induced apoptosis in ovarian cancer cells

Abstract: Abstract. There is considerable interest in redeploying drugs for use in combination with other oncology therapeutics. The single-agent activity of statins in ovarian cancer has been widely reported, however the drug concentration required to cause cell death is considerably higher than that achieved in patients receiving statin treatment for hypercholesterolemia. Unfortunately, statins can cause myopathy when administered in high doses. One solution to this is to identify drugs that could be used in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Multiple studies have utilized specific inhibitors of the pathway (AZD8835, AZD8186, and D-11688) and silencing RNA to increase the number of apoptotic cells in a dose-dependent manner, reduce anchorage-independent growth, and sensitize resistant cells to chemotherapy [ 251 , 252 , 253 ]. Interestingly, the combination of a PI3K pathway inhibitor with a BCL-2 family inhibitor showed synergistic effects in increasing cell death [ 254 , 255 ]. It could be that because of the many facets in the PI3K/AKT/mTOR pathway and the fact that the pathway itself has a major role in so many different cellular activities, inhibitors of PI3K/AKT/mTOR should be used in addition to inhibitors of other anti-apoptotic pathways in order to successfully enforce apoptosis in taxane-resistant cells.…”
Section: Taxane Resistance In Ovarian Cancermentioning
confidence: 99%
“…Multiple studies have utilized specific inhibitors of the pathway (AZD8835, AZD8186, and D-11688) and silencing RNA to increase the number of apoptotic cells in a dose-dependent manner, reduce anchorage-independent growth, and sensitize resistant cells to chemotherapy [ 251 , 252 , 253 ]. Interestingly, the combination of a PI3K pathway inhibitor with a BCL-2 family inhibitor showed synergistic effects in increasing cell death [ 254 , 255 ]. It could be that because of the many facets in the PI3K/AKT/mTOR pathway and the fact that the pathway itself has a major role in so many different cellular activities, inhibitors of PI3K/AKT/mTOR should be used in addition to inhibitors of other anti-apoptotic pathways in order to successfully enforce apoptosis in taxane-resistant cells.…”
Section: Taxane Resistance In Ovarian Cancermentioning
confidence: 99%
“…Recent studies found that statins sensitize cancer cells to intrinsic apoptosis by the novel class of apoptosis-inducing drugs BH3 mimetics [124,125]. Such agents induce rapid apoptosis when a cell is mitochondrially primed for death [126].…”
Section: Improving Statin Efficacy: a Focus On Mitochondriamentioning
confidence: 99%
“…Navitoclax also increased carboplatin sensitivity in one of three primary cultures derived from ascites. Later, other studies suggested that phosphatidylinositol 3-kinase (PI3K) pathway inhibitor (pictilisib) and navitoclax combination treatment resulted in enhanced pitavastatin-induced apoptosis in ovarian cancer cells [33]. This evidence suggests that Navitoclax is able to enhance the efficacy of chemotherapy drugs in ovarian cancer cells.…”
Section: Direct Targets In Apoptotic Pathwaysmentioning
confidence: 99%